"We're supposed to be a family here": An ethnography of preserving, achieving, and performing normality within methamphetamine recovery. (December 2021) - Brookfield, Samuel; Fitzgerald, Lisa; Selvey, Linda; Maher, Lisa
Abstract: The perception of being abnormal, and a visceral desire to 'feel normal again', is a common feature of the literature on drug use and recovery. Normality is constructed, however, in response to context-dependent values and priorities, thereby legitimating certain behaviours as normative and therefore the assumed goal of people in recovery. In this paper we draw on an ethnographic study with twelve people attempting to reduce harmful methamphetamine use to explore how they engaged with 'normality'. Semi-structured interviews and ethnographic observations were conducted across a range of settings related to participants' recovery, including private residences, withdrawal services, doctor's offices, counselling rooms, and court houses. We used a relational lens to conduct thematic analysis on interview transcripts and fieldnotes collected over six months, following the steps of Iterative Categorisation. Our analysis explores the central organising theme of normality as something that can be 'preserved', 'achieved', or 'performed' by people using methamphetamine. Findings are understood through the original concept of 'ambient paternalism', where neoliberal norms and values shape recovery trajectories even outside of engagement with services. Exhibiting normality enabled participants to work against the stigmatisation and moralisation of methamphetamine use by demonstrating their socio-political acceptability. Methamphetamine use could also be strategically used to enable participants to keep up with neoliberal normative standards of independent self-management. Increasing awareness of these complex repertoires of normality, and a more critical understanding of how this ideal is constructed and can impact service interactions, can support a less homogenising or coercive approach towards treatment and policy for people in methamphetamine recovery. Highlights: People using drugs can experience normality as aspirational and burdensome. Demonstrating normality in recovery can be a form of social capital. Normality can be a form of paternalism enacted by social services. Performing normality helped participants reduce their marginalisation.